Pharmacogenomics in psychiatry: Practice recommendations from an Asian perspective (2024) - Shih Ee Goh; Saumya Shekhar Jamuar; Siew Eng Chua; Derrick Chen Kuan Yeo; Jerome Hern Yee Goh; Chee Hon Chin; Mohamed Zakir Karuvetil; Ee Lian Lee; Daniel Shuen Sheng Fung; Giles Ming Yee Tan (Annals, Academy of Medicine, Singapore)
Introduction: Pharmacogenomic testing in psychiatry is an emerging area with potential clinical application of guiding medication choice and dosing. Interest has been fanned by commercial pharmacogenomic providers who have commonly marketed combinatorial panels that are direct-to-consumer. However, this has not been adopted widely due to a combination of barriers that include a varying evidence base, clinician and patient familiarity and acceptance, uncertainty about cost-effectiveness, and regulatory requirements. This review aims to examine recent updates in this field and provide a contextualised summary and recommendations for Asian populations in order to guide healthcare professionals in psychiatric practice. Method: A review of recent literature about current evidence and guidelines surrounding pharmacogenomics in psychiatric practice was carried out with particular attention paid to literature evaluating Asian populations. The Grading of Recommendations Assessment, Development and Evaluation Evidence to Decision framework was applied. Consensus meetings comprising workgroup psychiatrists from the public and private sectors were held prior to arriving at the key recommendations. Results: Pharmacogenomic testing should be mainly limited to drug-gene pairs with established clinical evidence, such as antidepressants and CYP2C19/CYP2D6. Direct-to-consumer pharmacogenomic panels that assay multiple genes and analyse them via proprietary algorithms, are not presently recommended in Singapore’s psychiatric setting due to inconclusive evidence on clinical outcomes. Conclusion: Pharmacogenomic testing in psychiatry is not recommended as standard clinical practice. Exceptions may include concerns about drug concentrations or potential severe adverse drug reactions. Studies investigating newly identified drug-gene associations, and clinical effectiveness and cost-effectiveness of utilising pharmacogenomic testing in psychiatry is encouraged.